PENGARUH STRATEGI GREEN MARKETING MIX DAN PENGETAHUAN PRODUK TERHADAP KEPUTUSAN PEMBELIAN (Studi Kasus Konsumen Ponsel NOKIA) - Fiona Annisa (Universitas Mercu Buana, 2015)
Abstract: This study aimed to identify and analyze the influence of green marketing mix strategy and product knowledge on purchasing decisions, consumer studies Nokia phone in Jakarta. Type of research design used was descriptive research, conducted at the biggest mobile phone mall ITC Roxy Mas, with 130 respondence during the period May to July 2014. Sampling techniques used was purposive sample to respondents who purchased Nokia. Thetools was used for the quantitative study, was a questionnaire. The final conclusion of green products, percieved price, distribution channel, promotion, and product knowledge was influence the purchasing decision either partially or simultaneously. The highest correlation dimensions of matrics coefficient was distribution channels variable with the purchase decision was extensive knowledge dimensions toward a personal factor which gained 0557. This research concluded that the company must to maintain the quality of Nokia phones that are characterized by eco-friendly at an affordable price, and introduce again to consumers through promotion and the right distribution channels, in order to increase consumer knowledge on environmental friendly products and ultimately stimulate to buy a Nokia phone.Keyword: Product, Percieved Price, Distribution Channel, Promotion, Product Knowledge, Purchase Decision